Utility of the Malayalam translation of the 7- minute screen for Alzheimer's disease risk in an Indian community. - de Jager, C; Thambisetty, M; Praveen, K; Sheeba, P; Ajini, K; Sajeev, A; Smitha, K; Rahmathulla, L; Ramakrishna, T; David, SA (2008)
BACKGROUND: Alzheimer's disease (AD) is suspected to be currently under-diagnosed in India, thus the need for a brief, effective screening test for the condition. AIMS: We aimed to test the Malayalam translation of the 7-Minute Screen (7MS) for detecting those at high risk for AD and to report on the subscores used to derive the Alzheimer's risk score. SETTING AND DESIGN: This study was performed in Kerala State amongst young university students and elders in residential care homes. MATERIALS AND METHODS: Two hundred and eighty-two volunteers were tested, 178 young controls (aged 20-29) and 104 literate elders, (55-92 years). None were clinically diagnosed with AD. STATISTICAL ANALYSES: Elders and controls were assessed as High or Low AD Risk with the published 7MS algorithm. Performance was compared between groups with ANOVA. RESULTS: The algorithm estimated high (n=61/104) or low (n=40/104) AD risk in the elderly. Significant differences were found between controls, low- and high-risk groups on all four components of the screen (Orientation: F=131.1, Enhanced Cued Recall: F=23.4, Clock Drawing: F=65.1, Verbal Fluency: F=15.7, P<0.0001 for all) and in the risk scores (F=144.7, P<0.0001). Age and gender affected verbal fluency, orientation and clock drawing performance. The high-risk group had worse scores for orientation and better scores for memory than previously reported for AD cases in other populations. CONCLUSIONS: The 7MS may be a useful screening test for cognitive impairment in India. Suggestions are given for revising the 'risk algorithm' for more appropriate AD risk assessment in this population.